1982
DOI: 10.1038/bjc.1982.313
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation by the human liver fluke, Opisthorchis viverrini, of the carcinogenic action of N-nitrosodimethylamine upon the biliary epithelium of the hamster

Abstract: Images Fig. 2 Fig. 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

1985
1985
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 12 publications
(7 reference statements)
0
18
0
2
Order By: Relevance
“…In several of the hamster studies, although fluke infection per se did not induce liver cancer, the combination of liver fluke infection and exposure to various carcinogenic nitrosamines induced cholangiofibrosis, cholangiocarcinomas, and hepatocellular nodules (9,10,(46)(47)(48). The high prevalence of Helicobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…In several of the hamster studies, although fluke infection per se did not induce liver cancer, the combination of liver fluke infection and exposure to various carcinogenic nitrosamines induced cholangiofibrosis, cholangiocarcinomas, and hepatocellular nodules (9,10,(46)(47)(48). The high prevalence of Helicobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…Many other experimental studies have found that other animals infected with C. sinensis alone have never developed cholangiocarcinoma, although the livers of animals experimentally infected with C. sinensis developed adenomatous hyperplasia, periductal fibrosis, inflammatory infiltration, and mucin-secreting cell metaplasia (66,67). Therefore, it has been suggested that the induction of cholangiocarcinoma from Clonorchiasis may be species dependent (61) and that the liver fluke per se does not provide the sole carcinogenic stimulus leading to malignancy (28).…”
Section: Experimental Studiesmentioning
confidence: 99%
“…Some investigations (28,61,110,113) have reported synergism between liver fluke infection and exogenous chemical carcinogens with respect to cholangiocarcinoma development in hamsters. Lee et al (61) demonstrated a high incidence (75%) of cholangiocarcinoma in hamsters that were treated with N-nitrosodimethylamine and then infected with C. sinensis.…”
Section: Experimental Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal experiments showed that N-nitrosodimethylamine could induce CCA in the Syrian Golden hamster [23] . Although OV infection alone did not induce CCA, the OV infection enhanced CCA production by N-nitrosodimethylamine in the hamsters [24,25] . Actually, a small amount of nitrosamine was detected in the food [4] .…”
Section: Etiological and Enhancing Agents For Cholangiocarcinogenesismentioning
confidence: 99%